Radical Romantics Prophets, Pirates, and the Space Beyond Nation - Ford, Talissa (Edinburgh Critical Studies in Romanticism : ECSR, 2022)
Examines dissident conceptions of space in the British Romantic eraGBS_insertPreviewButtonPopup(['ISBN:9781474409421','ISBN:9781474409445','ISBN:9781474409438']);Radical Romantics is about utopias and failed utopias, about cities that are palimpsests, and about the unwieldy span of the ocean. From William Blake's visionary poetry to Lord Byron's Eastern romances, from prophetic pamphlets to travel narratives, texts of the Romantic era make use of imaginative spaces to reveal the contours and limits of territorial sovereignty. In doing so, they raise fundamental questions about our understanding of both territorial and imagined space. What are the means by which people can conceive of geographical space without resorting to the terms of nationalism? Is it possible to imagine a space beyond territory, as movement itself? How can we articulate the overlap between mapped and lived space? Key Features Engages with the critical frameworks of cultural geography, cartography, and the burgeoning field of oceanic studiesReformulates theories of colonization and empire in the Romantic periodPuts canonical poetry in dialogue with travel tales and prophetic tracts